Information technology in audit processes: an empirical evidence from Malaysian audit firms - Mustapha, Mazlina; Soh, Jin Lai (Econjournals, 2017)
This paper attempts to highlight the usage of information technology for auditors at different levels and positions in audit firms in Malaysia. Factors influencing the usage of information technology in the audit processes are also investigated. Questionnaires were distributed to external auditors in Klang Valley. Descriptive statistics and regression analysis were carried out to analyze the data. Telephone interviews were also conducted to support the results. The result indicates that information technology is widely used in the audit processes. Information technology is especially used to generate the audit working papers and audited financial statements and to select samples during audit processes. The results indicate that information technology is mainly used by the senior auditors and audit managers in their organizations. The results appear to suggest that the auditors are motivated to use information technology because it helps to shorten the time of the audit process and get their job done in a more efficient manner.